Device modeling of RF varactor diodes for adjustable microwave reflectivity in active frequency selective surfaces. (11th June 2021) - Guo, Sai; Zhao, Yong; Cao, Zhaowang; Miao, Ling; Bie, Shaowei; Jiang, Jianjun
Abstract: At present, the design of absorbers with broadband electromagnetic absorption performance in the P/L band (0.3 ∼ 2 GHz) is a huge challenge. The frequency selective surface (FSS) loaded with active RF devices utilizes the characteristics of electrically adjustable device parameters, thereby a P/L band broadband active FSS absorber can be designed. It is obvious that device parameter characteristics are crucial to design excellent absorbing performance. Unfortunately, due to the industrial packaging characteristics of the current application of surface mounted devices, there are parasitic parameters in addition to the main impedance parameters. Here, an equivalent circuit model of a varactor diode is proposed. We combine thru-reflect-line calibration technology and advanced design system fitting to obtain the parasitic parameter values. Then a classic FSS structure is used to verify the consistency of the simulation and measurement for the varactor diode model. We hope that the model of the varactor diode we proposed will help the design of the new broadband adjustable absorber in the P/L band.